2015
DOI: 10.1186/s12885-015-1072-9
|View full text |Cite
|
Sign up to set email alerts
|

A phase II study of weekly irinotecan in patients with locally advanced or metastatic HER2- negative breast cancer and increased copy numbers of the topoisomerase 1 (TOP1) gene: a study protocol

Abstract: BackgroundAbout 20% of patients with primary breast cancer develop metastatic disease during the course of the disease. At this point the disease is considered incurable and thus treatment is aimed at palliation and life prolongation. As many patients will have received both an anthracycline and a taxane in the adjuvant setting, treatment options for metastatic breast cancer are limited. Furthermore response rates for the most commonly used drugs range from around 30% to 12% . Thus new treatment options are ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The efficiency and cytotoxic effect of the CPT may be regulated by other means than TOP1 expression and activity. Hence, the large variation in CPT response rates observed in small and non-randomized trials for BC may be due, at least in part, to a lack of reliable selective parameters for patient stratification [56].…”
Section: Discussionmentioning
confidence: 99%
“…The efficiency and cytotoxic effect of the CPT may be regulated by other means than TOP1 expression and activity. Hence, the large variation in CPT response rates observed in small and non-randomized trials for BC may be due, at least in part, to a lack of reliable selective parameters for patient stratification [56].…”
Section: Discussionmentioning
confidence: 99%
“…As an example, the pooled analysis of the Side Out 1 and 2 trials identified TOPO1 as a protein frequently overexpressed in MBC and as a potential predictor of response to irinotecan‐based treatment, as previously described [ 21 , 22 , 23 , 24 , 25 ]. Irinotecan as a single agent, when given after an anthracycline or taxane, has an objective response rate of 14% when given every 3 weeks and 23% when given weekly [ 26 ].…”
Section: Discussionmentioning
confidence: 88%
“…Data for TOP1-poisons in breast cancer is limited. Phase II trials in refractory patients have shown response rates similar to anthracyclines (30%) and taxanes (12%) versus 5–25% for irinotecan 30 , without stratifying patients. Our factor 12 points to tumors that are driven by ERBB-family members, growth factors, and hormone receptors (ESR1/AR).…”
Section: Resultsmentioning
confidence: 99%